2001
DOI: 10.1353/psc.2001.0026
|View full text |Cite
|
Sign up to set email alerts
|

Links between the Southern Oscillation Index and Hydrological Hazards on a Tropical Pacific Island

Abstract: River floods and hydrological droughts (low stream water resources) are a recurrent problem in different parts of Fiji, causing disruption and hardship for many rural communities. These extremes in fluvial behavior are associated with large seasonal variability in rainfall, generated by intense tropical storms in the wet season and prolonged rain failure in the dry season. Such conditions are linked to the influence of El Nino/Southern Oscillation (ENSO) in the Southwest Pacific. The Southern Oscillation Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
2
21
1
Order By: Relevance
“…5). Contrary to Kostaschuk et al (2001) and Terry et al (2001), who determined from a 30-year flow record that the peak discharge of TC-induced Rewa River floods was inversely related to the SOI, this study, using a much longer time series, could find no significant relationship between the peak heights of TC-induced Ba River floods and SOI (Fig. 5).…”
Section: El Niño-southern Oscillationcontrasting
confidence: 99%
See 2 more Smart Citations
“…5). Contrary to Kostaschuk et al (2001) and Terry et al (2001), who determined from a 30-year flow record that the peak discharge of TC-induced Rewa River floods was inversely related to the SOI, this study, using a much longer time series, could find no significant relationship between the peak heights of TC-induced Ba River floods and SOI (Fig. 5).…”
Section: El Niño-southern Oscillationcontrasting
confidence: 99%
“…1). Although Terry et al (2001) found the data useful for interpreting controls on low river flow, investigations in the course of this study showed that the record has little value for the analysis of floods: of the eight major floods recorded downstream , reliable flood discharges are available at Toge for only two-data gaps were found for four floods and probable data errors for another two. The Toge gauge has been washed away on several occasions and in 1999 the recorder stopped working as flood waters rose.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, Kane (1999) investigated characteristics and precipitation effects of the El Niño of 1997-1998. However, some of the previous research suggests that the ENSO is the most significant factor causing global hydroclimatic variability, especially in equatorial Pacific areas (Kahya and Dracup 1993, Allan 2000, Terry et al 2001, and a major controlling factor of inter-annual climatic variability in tropical regions like Indonesia (Aldrian and Susanto 2003, McBride et al 2003, Annas et al 2007). In Indonesia, ENSO events predominantly cause a reduction in rainfall that results in a longer dry season with greater water evaporation and a shorter rainy season with greater surface runoff.…”
Section: Enso-rainfall Relationshipmentioning
confidence: 99%
“…Hydrological studies in Fiji on ENSO-related storms demonstrate that cyclones during El Niño years produce higher amounts of stream discharge with subsequent flooding (Terry et al 1998(Terry et al , 2001. Substantial amounts of precipitation over brief time periods results in soil saturation and hazardous stream overwash (Terry et al 2001: 276-279).…”
Section: Environmental Contextmentioning
confidence: 99%